Implementation of Information System and Software Quality Testing in Company Operational Applications Based on ISO/IEC 25010: Case Study: PT Snapdev Digital Indonesia - Muhammad Alief Kemal; Salsa Apriliani Saka; Chairul Anwar (Switch : Jurnal Sains dan Teknologi Informasi, 2026)
Information system quality testing is a critical factor in supporting the effectiveness and efficiency of corporate business operations. This study aims to implement and evaluate software quality based on the ISO/IEC 25010 international standard within the E-Office (Digital Archive) operational applications of PT Snapdev Digital Indonesia. Quality testing is comprehensively conducted across eight main characteristics: Functional Suitability, Performance Efficiency, Compatibility, Usability, Reliability, Security, Maintainability, and Portability. The research methodology employs a quantitative descriptive approach using a structured questionnaire distributed to active users. Through purposive sampling, a final sample size of 27 active respondents was established. The empirical results show that the percentage scores for each quality aspect range from 80.00% to 86.67%, which demonstrates that the system successfully satisfies the standard software quality requirements. The overall average score of 83.56% places the system quality in the "Very Good" category. This outcome indicates that the system possesses efficient performance, strong security and reliability, ease of use, and adaptability across various environments. However, a minor area of improvement in security is identified to ensure optimal system protection. In conclusion, the implemented information system is highly suitable for supporting corporate operational needs and complies with international software engineering quality standards.